Genetic diversity in nine chickpea (Cicer arietinum L.) varieties based on different molecular markers - Begum, Kazi Nahida; Alam, Sheikh Shamimul (Bangladesh Journal of Botany, 2019)
Nine varieties (BARI Chola-1 to BC-9) of chickpea (Cicer arietinum L.) were studied with respect to isozymes, SDS-PAGE, amplified DNA produced by RAPD- and SSR-markers. The varieties could be characterized by SDS-PAGE bands on the basis of their location, size and intensity. Three isozyme systems, namely acid phosphatase, esterase and peroxidase were investigated of which esterase was found to be suitable for produced distinct polymorphic bands with 57.14% diversity. Ten RAPD primers were producing 74 bands with 93.24% polymorphisms which indicated highly diverse nature. In addition to polymorphism, 12 variety-specific RAPD fragments were identified. Ten SSR primer pairs were producing 20 distinct bands of which 11 were considered as polymorphic (55%). On the basis of RAPD and SSR analysis, BC-1 and BC- 6 were placed in cluster-1 and the remaining varieties were placed in cluster-2. On the other hand, the combined data of three isozymes systems and SDS-PAGE made BC-8 and BC-9 were different and thus placed in cluster-2 while the other seven varieties were placed in cluster-1.